DETERMINING THE BORDERS OF THE FEDERATED STATE AND THE ANALYSIS OF THE PARTIES’ APPROACH ACCORDING TO THE NEW SYSTEM WANTED TO BE ESTABLISHED IN CYPRUS - Soyalp TAMÇELİK (Fırat University, 2019)
The borders of sovereignty of the federated state according to the new system wanted to be established in Cyprus has been addressed in this research. In this context, the main purpose of this research is to display how internal sovereignty and administrative borders in the talks held between the sides in Cyprus will be determined and what can be done in relation to it. Actually, in the new system to be established by the Greeks in Cyprus for the Turks, the regional borders of each federated state will be determined more by quantitative values than quality. However, it has been established that these factors carrying a deterministic feature is based more on two principles. The first of these is that the proposals regarding territorial regulations must be able to achieve a definite, permanent, and just settlement. The second is that the creation of a bi-zonal, bi-communal, independent and detached Federated State of Cyprus will be a basis to the new Constitution to be formed. From this point of view, the creation of a federated state based on geographical features will only be possible in two ways. One of them is the Turkish view that both the states are protected in an absolute manner, a homogenous society exists in the concerning administrative zone and that the administrative borders are determined in accordance to this. The other is the Greek view that the island has been organized in a unitary way and the dynamics of society possessing heterogeneous characteristics are shaped. Based on this fact, the research consists of two main sections. In the first section, determining the administrative or regional borders of the state wanted to be established in Cyprus and the analysis of concepts related to this have been addressed and examined. In the second and final section, the analyses of the stances of the Turkish and Greek Cypriots have been evaluated.